5Ps: Governance and performance measurement framework for social enterprises in creating social values to society / Saunah Zainon, Soo Kum Yoke and Isma Ishak - Zainon, Saunah; Soo, Kum Yoke; Ishak, Isma (UiTM Cawangan Johor, 2019)
The trend of Social Enterprise (SE) operations has been on the rise globally. Achieving momentum for social values to societies although may be challenging, has been seen as necessary in businesses especially in addressing social issues such as unemployment and environmental problems. SEs are run by social entrepreneurs who combine the spirit of entrepreneurship and community to build social capital towards community improvement. As such, social capital navigates the use of the concept of SEs. It is this social relationship that glues societies together and enables them to get along with one another. The elements of trust, civic spirit, solidarity and readiness drive social capital to move SEs to build and maintain communities. What is important to note is the fact that, even though the numbers in studying SEs are growing, less attention is being paid to the governance and performance measurement of SEs particularly in Malaysia. Thus, this paper aims to propose a governance and performance measurement framework for SEs in creating social values to society. With the governance and performance measurement framework, social enterprises could be moulded to improve the quality of life of poor and disadvantaged people, in line with the government's New Economic Model (NEM), that includes poverty eradication. Hence, this would be useful to interested parties to establish any form of SEs. In addition, relevant governmental agencies would be able to regulate and monitor the establishments of SEs in the context of governance.